2015
DOI: 10.1007/s10973-015-4874-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size reduction and crystalline form on dissolution behaviour of nimesulide

Abstract: The objective of this study was to develop and examine innovative and very simple and easily scalable techniques able to improve solubility and/or dissolution rate and thus oral bioavailability of nimesulide. Three different nimesulide batches were obtained by three different laboratory-scale methods: Method A (Batch A) used crystallization by solvent evaporation in a nanospray dryer, Method B (Batches G and GLN) involved cryo-milling, and Method C (Batch Neu) dispersed nimesulide in Neusilin(A (R)) UFL2. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Studying the nanocrystal structure of a nimesulide drug, the scientists found that better solubility of BCS Class II drugs (including nimesulide) in water can be achieved by reducing the particle size using nanotechnologies. It is also confirmed by R. Rascioni et al.’s study [ 40 ], which found a relation between the reduction of the nimesulide particle size and the increased dissolution rate.…”
Section: Discussionsupporting
confidence: 78%
“…Studying the nanocrystal structure of a nimesulide drug, the scientists found that better solubility of BCS Class II drugs (including nimesulide) in water can be achieved by reducing the particle size using nanotechnologies. It is also confirmed by R. Rascioni et al.’s study [ 40 ], which found a relation between the reduction of the nimesulide particle size and the increased dissolution rate.…”
Section: Discussionsupporting
confidence: 78%
“…Effective delivery of Biopharmaceutics Classification System class II active pharmaceutical ingredients (APIs), defined as having high permeability and low solubility, 1 is challenging due to their low bioavailability. 2 To enhance their bioavailability, several technologies have been examined, such as particle size reduction, [3][4][5] cyclodextrin complexes, 6 polymeric micelles, 7 freeze-dried liposomes, 8 solid lipid nanoparticles, 9 and amorphous solid dispersions (ASDs). 10,11 Among them, amorphous solids dispersions technology has been proved to be one of the promising solutions.…”
Section: Introductionmentioning
confidence: 99%
“…• inflammation (e.g. dexamethasone and azithromycin, or pain and fever reducer indomethacin and nimesulide) [16,31,45,47,48,53,55,64,71,[99][100][101],…”
Section: Applications Of Nano Spray Dried Pharmaceuticals On the Labomentioning
confidence: 99%
“…• oral (e.g. poorly water-soluble drugs like diuretic furosemide [10], pain reducing nimesulide [100], blood vessels dilating nicergoline [67], fever reducing indomethacin [99], anti-inflammatory dexamethasone [46], or steroidal hormone mecigestone [109]),…”
Section: Applications Of Nano Spray Dried Pharmaceuticals On the Labomentioning
confidence: 99%